Innovative 21st Century Learning Through PAKEM Learning Management - Debie Kalalo; Deitje Katuuk; Jeffry Lengkong; Victory Nicodemus Joufree Rotty (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
21st Century Learning is learning with a new paradigm that is oriented towards learning new literacy, namely human literacy, data and technology. More specifically, mastery of 21st century skills, namely life and career skills, innovation and learning skills, and information, media, and ICT skills. The characteristics of learning to practice these essential skills lead to an interactive, holistic, integrative, scientific, contextual, thematic, effective, collaborative, and learner-centered learning process, so that in its implementation educators can design activities by choosing learning methods/models that can accommodate all of these characteristics in a comprehensive manner. In line with PAKEM learning which originates from the concepts of student-centered learning and learning is fun, so that students have the motivation to always learn without orders and they don't have feelings of heaviness and fear. Thus, the aspect of fun is learning and motivating students to explore, actively create and experiment continuously in the learning process becomes a significant aspect in the PAKEM learning process. In learning management there are three learning steps. The three steps include: 1), planning of the PAKEM learning process. Planning of the PAKEM learning process can be done when educators design syllabus and lesson plans; 2), implementation of PAKEM learning. This implementation is the application of the lesson plan. This implementation consists of preliminary, core and closing PAKEM learning activities; and 3) PAKEM learning evaluation. The PAKEM learning evaluation/assessment stage is a follow-up in the PAKEM learning process activities. Mission/Purpose of PAKEM learning evaluation is an effort to identify and understand the level of success in the learning process. Thus, innovative learning in the 21st century creates human resources who are literate in information, data, and technology which are needed to face the competition in life and the job market in the current and future globalization era.